MicroRNA-129-3p Suppresses Tumor Progression and Chemoradioresistance in Head and Neck Squamous Cell Carcinoma - Tae Mi Yoon; Sun-Ae Kim; Eun Kyung Jung; Young-Kook Kim; Kyung-Hwa Lee; Sang Chul Lim (Current Oncology)
(1) Background: MicroRNA-129 (miR-129) participates in tumor progression and chemoresistance in various cancer types. In this study, the role of miR-129-3p, the main mature form of miR-129, in tumor progression and chemoradiotherapy resistance in head and neck cancer was evaluated. (2) Methods: RT-PCR, western blotting, cell proliferation assays, cell apoptosis assays, and cell invasion and migration assays were used. (3) Results: In this study, the miR-129-3p overexpression suppressed the proliferation, invasion, and migration of SNU1041, SCC15, and SCC25 human HNSCC cell lines. Additionally, it induced apoptosis and enhanced radiation-/cisplatin-induced apoptosis of SNU1041, SCC15, and SCC25 cells. Therefore, miR-129-3p could suppress tumor progression and enhance chemoradiosensitivity in human HNSCC. Furthermore, miR-129-3p was downregulated in fresh tumor tissues from patients with HNSCC compared with that in the adjacent normal mucosa. In a nude mouse xenograft model with SNU15 cells, the miR-129-3p overexpression significantly decreased tumor growth, as measured by tumor weight and volume. (4) Conclusions: Our study provides evidence that miR-129-3p suppresses tumor progression and chemoradioresistance in HNSCC. This finding may serve as a basis for developing miR-129-3p-based therapeutic strategies.